UPAYA MENINGKATKAN PEMAHAMAN FISIKA MELALUI METODE PBL (PROBLEM BASED SOLVING LEARNING) PADA SISWA KELAS X SMA NEGERI 2 RAMBAH T.P 2015/2016 - Novita Handayani (JURNAL PENDIDIKAN ROKANIA, 2021)
This research is a classroom action research, which aims to improve the understanding of physics by using the Problem Based Learning method. This classroom action research consists of 2 cycles, the first cycle with four actions or learning meetings and the second cycle with three actions. The results of data analysis were carried out by observing, presenting questionnaires and learning outcomes tests. The ability improvement data is based on the first cycle test average value of 75.7; second cycle test 77.5; and the third cycle test is 85.6. The percentage of students who scored above the KKM in the first cycle was 40% or 10 students, the situation increased to 60% or 15 students in the second cycle, and in the third cycle it reached 100% or 25 students. From these results it can be said that this management can occur in stages by evaluating and reflecting on the previous cycle. By continuing to train scientific methods in each lesson, students will feel meaningful learning and understanding in learning can be achieved with results as expected